A Comment on Measuring Horizontal Equity - Plotnick, Robert (Quarterly Journal of Economics, 1980)
Journal Article A Comment on Measuring Horizontal Equity Get access Robert Plotnick Robert Plotnick Dartmouth College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 95, Issue 2, September 1980, Pages 383–385, https://doi.org/10.2307/1885507 Published: 01 September 1980